KEPEMIMPINAN TRANSFORMATIF PADA DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU TAHUN 2022-2023 - Andini, Rani; ,, Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Transformational leadership has gained attention in the public sector, Transformational leadership has gained attention in the public sector, particularly in how a leader motivates employees to be more innovative and loyal to their performance in order to realize good governance. One example of transformational leadership can be seen in the Department of Environment and Sanitation of Pekanbaru City. This study aims to examine the transformational leadership of the head of the Department of Environment and Sanitation of Pekanbaru City in 2022–2023 based on the theory of transformational leadership. The research method used in this paper is a qualitative descriptive approach, with data collection techniques through interviews and documentation studies. The data were analyzed using the theory of transformational leadership by Bernard M. Bass, which includes four main indicators: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. The results of the study show that the transformational leadership of the head of the Department of Environment and Sanitation of Pekanbaru City has not fully aligned with the execution of core duties and functions. In the aspect of program and budget planning, there are still weaknesses in accountability, indicating a lack of idealized influence. The lack of innovation in addressing waste issues also shows that intellectual stimulation has not been optimal. On the other hand, the lack of attention to employees reflects the underdeveloped practice of individualized consideration. Moreover, the leadership vision has not fully inspired all staff to improve their work performance (lack of inspirational motivation). To improve transparency and accountability in budget management and policy-making, leaders need to create a work environment that fosters enthusiasm, encourages the exchange of ideas, opens up discussion forums, and holds training programs to develop employee capacityF Keywords: Leadership, Transformative , Transformative Leadership